Tracing Themes of the Prophet’s Preaching in the Qur’an Tartibun Nuzul Perspective - Djidin, M (Ekspose: Jurnal Penelitian Hukum dan Pendidikan, 2024)
The aim of this research was to trace and analyze the themes of the Prophet Muhammad's preaching based on the order of revelation. This study explored the thematic evolution of the Prophet's messages during the Mecca and Medina periods and assessed their relevance to the da'wah context of the time. Using a qualitative, literature-based method with a Tartibun Nuzul approach, the findings revealed that the early da'wah focused on aqidah and monotheism, gradually expanding to include social, ethical, and sharia law issues in response to the evolving dynamics of Arab society. This research provided a new perspective on the Prophet's da'wah strategy and its implications in a modern context.